Аnalytical upshots of unstationary transfer of mass and heat are at maximum terms of the third family - Knysh, Yuriy (Forestry, Forest, Paper and Woodworking Industry, 2007)
In work the upshots ofunstationary transfer of mass and heat are presented at the maximum terms of the third family.